Identification of leakage in ball valves by analysis of pressure and torque signatures in cyclical tests under critical operating conditions - Teles, Diógenes Barbosa (2021)
Prototypes of Trunnion ball valves fitted with Scotch Yoke actuators have been submitted to opening and closing cycling tests so as to monitor and analyze their operation under critical conditions in order to evaluate their failure modes. The prototypes were arranged so as to collect data related to pressures, torques, temperatures and angular positions from the valve balls during the tests. Pressure signatures of the hydraulic actuator and stem torques were generated through the data collected and analyzed using the moving variance method. Also analyzed were the upstream and downstream pressure signature profiles of the valves throughout the test. It was found that the critical components for these pieces of equipment were the seals, called seats, which are produced from reinforced polytetrafluoroethylene (RPTFE). The seats showed considerable plastic deformations under the test conditions, which eventually lead to the rupture of the sealing band, resulting in leakages. When combining the analysis of the moving variance method with the analysis of the pressure signature profiles, changes were detected in the behavior of the prototypes throughout the tests, in addition to indicating the moment of failure. This methodology can be useful for prototype evaluations and even for valve instrumentation in the field, so as to ensure greater reliability, prevent unnecessary maintenance and provide safer operating conditions.